2022
DOI: 10.1002/cam4.4603
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the prognostic and role in immune cell infiltration of MSR1 expression in lower‐grade gliomas

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…We hypothesized that overactivation or increased expression levels of MSR1 and BIRC5 could promote malignant behavior in LGG.Evidences have revealed that BIRC5 can promote cell proliferation and anti-apoptosis in gliomas [ 35 ]. MSR1 is a marker of M2 macrophages, and has been shown higher expression in patients with gbm compared to those with grade II gliomas, which indicated that MSR1 may exert cancer-promoting effects [ 36 , 37 ]. To verify the screened robust m1A-RDEIGs (MSR1 and BIRC5) in LGG and corresponding normal cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that overactivation or increased expression levels of MSR1 and BIRC5 could promote malignant behavior in LGG.Evidences have revealed that BIRC5 can promote cell proliferation and anti-apoptosis in gliomas [ 35 ]. MSR1 is a marker of M2 macrophages, and has been shown higher expression in patients with gbm compared to those with grade II gliomas, which indicated that MSR1 may exert cancer-promoting effects [ 36 , 37 ]. To verify the screened robust m1A-RDEIGs (MSR1 and BIRC5) in LGG and corresponding normal cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…CD80 or CTLA4 is a known co-inhibitory receptor present in Tregs and antibodies targeting this protein like ipilimumab has shown to produce clinical activity. MSR1 has been described as present in M2 macrophages contributing to inflammation and patient outcome 27 , 28 . Indeed, presence of MSR1 has been linked with T cell exhaustion and it has been included in a gene signature that predicted favorable response to anti PD (L)1 in liver cancer 29 .…”
Section: Discussionmentioning
confidence: 99%
“…MSR1 demonstrated a 6-fold increase (mRNA expression of 2.3 ± 0.07, p < 0.0001) and CD86 showed an 8.9-fold increase in expression (mRNA expression of 2.41 ± 0.06, p < 0.0001) in LGG tumors. Expression of the M2-like TAM marker MSR1/CD204 [ 37 ] was found to be an independent prognostic factor for LGG patients and may play a vital role in their immunotherapy [ 41 ]. CD86 is expressed on M1-like and M2b-like macrophages [ 23 , 37 ] and may contribute to an immunosuppressive TME through activation of CD4+FoxP3+ regulatory T cells (Treg) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%